Comparative Evaluation of Enalapril and Losartan in Pharmacological Correction of Experimental Osteoporosis and Fractures of Its Background - D. S. R. Rajkumar; A. V. Faitelson; O. S. Gudyrev; G. M. Dubrovin; M. V. Pokrovski; A. V. Ivanov (Journal of Osteoporosis)
In the experiment on the white Wistar female rats (222 animals), the osteoprotective effect of enalapril and losartan was studied on experimental models of osteoporosis and osteoporotic fractures. It was revealed that in rats after ovariectomy, the endothelial dysfunction of microcirculation vessels of osteal tissue develops, resulting in occurrence of osteoporosis and delay of consolidation of experimental fractures. Enalapril and losartan prevented the reduction of microcirculation in bone, which was reflected in slowing the thinning of bone trabeculae and in preventing the occurrence of these microfractures, as well as increasing quality of experimental fractures healing.